Growth dynamics of plexiform neurofibromas: a retrospective cohort study of 201 patients with neurofibromatosis 1 - Nguyen, Rosa (BioMed Central, 2012)
BACKGROUND: To examine the natural growth dynamics of internal plexiform neurofibromas (PNs) in patients with neurofibromatosis 1 (NF1). METHODS: Two hundred and one NF1 patients underwent whole body MRI (WBMRI). Tumour burden was estimated volumetrically. Non-parametric Spearman’s rho correlation coefficients were used to analyse the relationship of growth rate to tumour volume and age. Chi-squared and Mann–Whitney U tests were used for analysing the association of tumour occurrence with sex or age. Chi-squared tests were used to analyse the association of tumour growth with age group. RESULTS: Seventy-one of 171 patients with serial WBMRI exams had internal PNs (median follow up 2.2 years [1.1 to 4.9 years]). Median whole body tumour volume was 86.4 mL [5.2 to 5878.5 mL]) with a median growth rate of 3.7%/year (−13.4 to 111%/year) that correlated with larger whole body tumour volume (P<0.001) and lower age (P=0.004). No new PNs developed in 273.0 patient-years among patients without tumours. Rate of new tumour development among patients with PNs was 0.6%/year (95% confidence interval 0.02 to 3.4%). Twenty-seven (13.5%) tumours increased significantly and were more frequent among children (P<0.001). Growth rate of tumours was inversely correlated with age (Spearman’s rho=−0.330, P<0.001). Seventy-one (35.5%) tumours had smaller volumes on follow up (median −3.4%/year [−0.07% to −35.9%/year]). CONCLUSION: Children with NF1 and internal PNs are at risk for tumour growth. Most PNs grow slowly or not at all, and some decrease in size. New tumours are infrequent in NF1 patients with PNs and unlikely in patients without PNs.